The association constant of 5′,8-cyclo-2′-deoxyguanosine with cytidine - Capobianco, Amedeo; Caruso, Tonino; Fusco, Sandra; Terzidis, Michael A.; Masi, Annalisa; Chatgilialoglu, Chryssostomos; Peluso, Andrea (Frontiers in Chemistry, 2015)
The association of 5',8-cyclo-2'-deoxyguanosine (cdG), a DNA tandem lesion, with its complementary base cytosine has been studied by voltammetry and NMR in chloroform, using properly silylated derivatives of the two nucleobases for increasing their solubilities. Both voltammetric data and NMR titrations indicated that the Watson-Crick complex of cytidine with cdG is weaker than that with guanosine, the difference being approximately of one order of magnitude between the two association constants.